Criterion for assessing the causes of road accidents according to a specific age group of drivers in Poland based on road incidents occurred in 2020 - Podgórska, Agnieszka; Rajchel, Jan; Kępa, Paweł (Polityka i Społeczeństwo, 2023)
This research analyses the main causal factors that lead to road accidents. Particular focus has been on the demographics of drivers and in particular on the age group given that younger drivers account for the highest number of road safety-related incident/ accidents and fatalities. Other factors impacting road safety include the adequacy of the national driver training system, legislative requirements and organisational solutions for ensuring road safety. Behavioural and characteristics of drivers are considered as part of the causal analysis.